Masks – from skin to portrait - Németh, Domonkos; Fedor, Ilka (ARTCADIA, 2024)
In her work titled Suaire, Odile Bernard Schröder applies cream and charcoal to the face of her model, then removes this layer with transparent adhesive tape, which she sticks onto plexiglass to create a contact print. In his work Dermography, János Iván Kárpáti also uses adhesive tape to take skin and hair samples from faces. He arranges the strips of tape on black paper, scans them and prints their image. In her work Mask, Ilka Fedor reflects on the phenomenon of drag queens by removing makeup from a face with adhesive tape thus creating a portrait she can then contact print and enlarge. Comparing these very similar artworks reveal their crucial differences, and shows us that the boundaries between the face and the mask are just as blurred as the boundaries between image and reality.